Respuesta :
Step-by-step explanation:
Let's assume that the dryer costs x $.
Then the washer costs x-73$, 73$ dollars less.
If we add the two costs together we get that: x+x-73 = 677 <-> 2*x = 750 <-> x=375$
The dryer costs x=375$
Answer:
The cost of the dryer is $375
Step-by-step explanation:
We call w the cost of the washing machine and we call d the cost of the dryer
We know that together they cost $ 677
This means that:
[tex]w + d = 677[/tex]
We also know that the washer cost $ 73 less than the dryer
This means that:
[tex]w = d-73[/tex]
Now we substitute the second equation in the first and solve for d:
[tex]d-73 + d = 677[/tex]
[tex]2d= 677+73[/tex]
[tex]2d=750[/tex]
[tex]d=\frac{750}{2}[/tex]
[tex]d=\$\ 375[/tex]